Gestão escolar e escola democrática: ações e reflexões - Prado, Joao Ferreira do (2003)
This work is a result of several questions raised up along the professional trajectory as a teacher and director in public schools of São Paulo City, in São Paulo State, Brazil. Though that professional experience it is possible to deal whit some present school characteristics: reduction of autonomy, centralization of authority, lack of compromise in relation to the learning process and unsatisfactory educational results. Among other steps to change this framework, it is necessary to trigger a shifting process to promote changes aiming, mainly, the participation of all school community in the processes of decision make up related to school problems and, this way, contributing to the school democratization. From the general framework of the school reality, the objective is to develop future plans and programs in order to help it to become more democratic and participant To study questions and reflect about school management is the main justifying of this work, aiming its democratization and the possibility of broadening the access of social opportunities of life in society. The main basic subjects were developed in order to understand better the styles of democratic and collegiate administration. The procedures utilized in this study were participant observation and interview in group. The results of this research allowed the identification of the problems, a survey of questions and deep reflections about school reality. Those results suggest a continuity of this study with new challenges, major ampleness, another directives and tools